Stigmatized Identity in The Myth of Dewi Ontrowulan - Andalas, Mutiara (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
The dissociation of Dewi Ontrowulan from the pilgrimage site of Mount Kemukus and the participation of women in the sex ritual excite me to explore her myths. Surveying the various myths about Dewi Ontrowulan, this paper seeks to sketch the possibly dominant characterization of her. Besides her absence in providing blessings to pilgrims, her presence at the pilgrimage ritual greatly contributes to the brokenness of women’s bodies there. I apply feminist phenomenology to unveil the hiddenness of crimes against women. Reconstructing a liberating myth of Dewi Ontrowulan necessitates the de-stigmatization of her stigmatized character. A feminist re-reading on her myths hopefully also contributes to the liberation of these women from stigmatization.